FENOMENA KOMUNIKASI ANGGOTA KOMUNITAS GRAFFITI DI KOTA MEDAN (Studi Fenomenologi Pada Anggota Komunitas ME&ART) - Fitri Lestiara Sani; Nova Yohana (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
Community of Graffiti become a separate phenomenon, which represent one of the subkultural youngster in the middle of society. Community of ME&ART in Medan become a unique phenomenon, because specification and uniqueness of activity and also life style which this community have to make this community exist and recognized in Medan. Some ways do youngster to communicate the existence of self through art of graffiti. This research intend to know motive of member community ME&ART in expressing art of graffiti, symbol meaning of graffiti and for describe about communication behavior of community member ME&ART in Medan.This research used qualitative methode by phenomenological approach. The subject of research is 5 who represent Community member of ME&ART selected use technique of purposive. Data obtained through participant observation, in-depth interview, and documentation. This research use technique analyse data of interaktif by using data collecting technique, data discount, presentation of data and withdrawal of conclusion.The result of research showed that here are two motives of community members to express their graffiti art motifs of the past and the future motives. Meaning built by members of the community ME&ART Graffiti as a medium to deliver creative, media delivery of messages and as a medium of expression. Community members communication behavior ME & ART views of verbal communication verbal and nonverbal communication.Keywords: Phenomenological, graffiti, Community, Meaning of Symbols, Communication Behavior, Simbolic Interaction Theory.